Antihyperpigmentation Effect of The Combination of Turmeric (Curcuma domestica Val.) and Bitter Melon Leaves (Momordica Charantia L.) Ethanol Extracts on Guinea Pig Skin - Fitria, Risha Fillah; Anas, Yance; Safitri, Erika Indah (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2018)
Turmeric (T) and Bitter Melon leaves (BM) extract has been proven in decreasing melanin contents in in vitro study, but their single extracts effects were lower than the positive control. A study confirmed the combination of plants extracts had melanogenic effect better than the positive control and their single extracts. This study aimed to investigate the anti-hyperpigmentation effect of the combination of T and BM extract on guinea pig skin and compared with the positive control group. This study used a post-test control design. Twenty-five guinea pigs were divided into 5 groups. The negative control group was given by dimethyl sulfoxide; the positive control group was given by a pharma cream that consists of hydroquinone, tretinoin, and fluocinolone acetonide. The combination of extracts was given to experimental groups with doses 500 μg/mL of T and 200 μg/mL of BM; 750 μg/mL of T and 400 μg/mL of BM; 1.000 μg/mL of T and 600 μg/mL of BM, respectively. All groups exposed to UV-B light in 2 minutes/day for 2 weeks. Each experimental group was given 1 ml combination extract once a day for 2 weeks and in the last step, skin biopsies were done. The histopathological examination was conducted by staining with Fontana-Masson and Nuclear Fast Red. The average percentage of melanin area were compared in all group and analyzed with the Kruskal Wallis test followed by Mann-Whitney test with 95% of confidence level. The result showed group-2 and 3 had the better effect than pharma cream.